The mechanical properties of anisotropic polymers: Progress report no. 6 - Darlington, M. W. (College of Aeronautics, 1968)
Part 1 General Developments The basic development work on the tensile creep apparatus was completed by March, 1968. A description of the latest 'heavy-duty' creep rig and two types of contraction extensometer, together with the relevant creep trials, was given in Progress Report No. 5. Since then two further 'heavy-duty' creep rigs have been assembled and tested and are now ready for use with rigid plastics. In addition, further trials of the double transducer contraction extensometer described in Report No. 5 have been carried out. These trials are described in part 2 of this report The trials were considered reasonably satisfactory and each of the three heavy-duty creep rigs has now been fitted with a device of this type in addition to the normal tensile extensometer. The polythene creep rig described in Progress Report No. 3 has been working satisfactorily for over a year and no further modifications have been made in the period under review. At the conclusion of the above-mentioned trials it was considered that the creep apparatus was unlikely to require any further major changes. A detailed report of all the apparatus has therefore been prepared with the intention of submitting it for publication to the Journal of Scientific Instruments. It is at present being examined at the Ministry of Technology. (CoA Memo. No. 158).